1994
DOI: 10.1180/claymin.1994.029.3.01
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium coordination and structural disorder in halloysite and kaolinite by 27Al NMR spectroscopy

Abstract: A B S T R A C T:It has been suggested that interlayer water in halloysite is due to the presence of hydrated cations that balance the negative layer charge produced by AI for Si substitution. To find evidence of 4-coordinate AI (AI(IV)), we investigated six halloysites and two kaolinites using 'high-field' and 'mediumfield' solid-state 27A1 MAS NMR spectroscopy. We found AI(IV) in both kaolinite and five halloysite samples, but the contents are all <1% and provide no basis for distinguishing between kaolinite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 17 publications
(20 reference statements)
2
11
1
1
Order By: Relevance
“…The 27A1-MAS-NMR confirms a disorder in kaolinite structure arising as a result of Al-vacancy displacements in the octahedral sheet (Newman et al, 1994). The three spectra of kaolinite samples have a similar shape and no major differences between the kaolinite spectrum and the halloysite spectrum could be detected.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The 27A1-MAS-NMR confirms a disorder in kaolinite structure arising as a result of Al-vacancy displacements in the octahedral sheet (Newman et al, 1994). The three spectra of kaolinite samples have a similar shape and no major differences between the kaolinite spectrum and the halloysite spectrum could be detected.…”
Section: Discussionsupporting
confidence: 50%
“…The full-width-at halfmaximum (FWHM) of this line increases from 9.4 ppm for well-ordered kaolinite to 10.00 ppm for halloysite, whereas for poorly-ordered kaolinite it is 10.8 ppm. The increasing FWHM of this resonance is due to a larger distribution of quadropole coupling parameters and isotropic chemical shifts brought by structural disorder that arises primarily as the result of Al-vacancy displacements in the octahedral sheet (Newman et aL, 1994). In addition to the six-coordinated aluminum peak, the spectrum of poorly-ordered kaolinite displays a resonance at --70 ppm attributed to four-coordinated aluminum.…”
Section: Zal-magic Angle Spinning Neutron Magnetic Resonancementioning
confidence: 97%
“…This negative correlation between Fe content and LB contrasts the observation and conclusions of Newman et al (1994). They suggest paramagnetic dipole-dipole interactions between structural Fe and A1 as the main cause for line broadening in halloysites.…”
Section: Nmr Line Broadening Effectscontrasting
confidence: 52%
“…Due to the extremely small size of Hal nanotubes, it also had excellent boundaries and surface activity, so that its CEC value increased with decreasing sizes. Bailey (1990) considered Al 3+ substituted Si 4+ cations in the halloysite tetrahedron to produce negative charges [51], however, the 27 Al NMR by Newman et al (1994) [52] indicated that halloysite has similar Al(IV) content as standard kaolinite. This charge was balanced by the interlayer surface hydration exchangeable cations.…”
Section: Cec Analysismentioning
confidence: 99%